2013
DOI: 10.1158/0008-5472.can-12-4358
|View full text |Cite
|
Sign up to set email alerts
|

Indirubin Derivative 6BIO Suppresses Metastasis

Abstract: While metastasis is the chief cause of cancer mortality, there nonetheless remains a lack of antimetastatic therapies that are clinically available. In this study, we present the indirubin derivative 6-bromo-indirubin-3 0 -oxime (6BIO) as a promising antimetastatic agent. 6BIO strongly reduced formation of lung metastasis in the well-established 4T1 mouse model of aggressive breast cancer. Several major hallmarks of the metastatic process were affected by subtoxic concentrations of 6BIO, which inhibited adhesi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 46 publications
2
25
2
Order By: Relevance
“…26 Strikingly, we found that it also represses both the AR and the AR-V7 gene expression as a single agent, and it enhances AR-ASO function when the ASO is delivered by gymnosis to prostate cancer cells. To our knowledge, there is no therapeutic agent currently available that can effectively repress the AR-V7 splice variant.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…26 Strikingly, we found that it also represses both the AR and the AR-V7 gene expression as a single agent, and it enhances AR-ASO function when the ASO is delivered by gymnosis to prostate cancer cells. To our knowledge, there is no therapeutic agent currently available that can effectively repress the AR-V7 splice variant.…”
Section: Introductionmentioning
confidence: 74%
“…These include the CDK family members CDK1, CDK2, and CDK5, in addition to PDK1, JAK/STAT3, and GSK-3a/b. 22,26,40,[43][44][45] GSK-3a/b is a ubiquitously expressed serine-threonine kinase encoded by distinct genes. 47 The two isoforms share 97% sequence homology within their catalytic domains but differ in their C and N termini.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, drugs that can block the metastatic spread of cancer cells would have a major impact on cancer patient survival. Employing the 4T1 mouse model of aggressive breast cancer, it was observed that 1 mg/kg BIO pre-treatment dramatically reduced lung metastasis 8 days after intravenous delivery of cancer cells (Braig et al 2013). BIO treatment reduced the cell invasiveness by down-regulating expression of the pro-migratory factors, C-terminal tensinlike protein, and matrix metalloproteinase 2, which was also linked to inhibition of the JAK/STAT3 pathway.…”
Section: Bio Reversinementioning
confidence: 98%
“…These deep roots made possible the successful application of in silico rational drug design in a growing number of cases: (1) the so-called hybrid-design was carried out, in which the same kinase inhibitor targets different protein regions, thus merging the characteristic of potency (typical of first generation inhibitors) and selectivity (obtained by second generation ones) (Albaugh et al, 2012); (2) imatinib was also reengineered to reduce its cardiotoxicity, by making use of a different water propensity of two residues in the principal and secondary target kinases (Fernandez et al, 2007). Several MD simulations were carried out at this scope, that were able to discriminate the dynamic and structural characteristics of Bcr-Abl and C-Abl kinases, this last responsible for the cardiotoxic effects; (3) systematic rigid body docking of potential inhibitors against 84 unique protein kinases identified three derivatives of indirubin (Zahler et al, 2007), one of which has been recently indicated as particularly active against cancer metastasis (Braig et al, 2013). …”
Section: Inhibitorsmentioning
confidence: 99%